KONSIDERASI UNTUK MENERAPKAN STUDENT GROUPING DALAM PEMBELAJARAN TATA BAHASA TOEFL DENGAN MENGGUNAKAN APLIKASI NST TOEFL EXPLORER - Barotun Mabaroh; Diah Anita Pusparini (Pusat Pengembangan Bahasa IAIN Tulungagung, 2018)
Lecturers must consider many things before implementing strategies in the learning process. This is because learning strategies also affect students’ learning outcomes. Once, low-achiever students can improve their competence because of the working strategies. Contrarily, high-achiever students may get decreased because of the worst strategies. From various strategies in the learning process, student grouping is a popular strategy which supports collaboration among students. Yet, the lecturer must be able to consider several things related to student grouping. The main consideration is “with whom” and “how” students should be grouped.